MiR-140 leads to MRE11 downregulation and ameliorates oxaliplatin treatment and therapy response in colorectal cancer patients - Horak, Josef; Dolnikova, Alexandra; Cumaogullari, Ozge; Cumova, Andrea; Navvabi, Nazila; Vodickova, Ludmila; Levy, Miroslav; Schneiderova, Michaela; Liska, Vaclav; Andera, Ladislav; Vodicka, Pavel; Opattova, Alena (Frontiers in Oncology, 2022)
Cancer therapy failure is a fundamental challenge in cancer treatment. One of the most common reasons for therapy failure is the development of acquired resistance of cancer cells. DNA-damaging agents are frequently used in first-line chemotherapy regimens and DNA damage response, and DNA repair pathways are significantly involved in the mechanisms of chemoresistance. MRE11, a part of the MRN complex involved in double-strand break (DSB) repair, is connected to colorectal cancer (CRC) patients’ prognosis. Our previous results showed that single-nucleotide polymorphisms (SNPs) in the 3′ untranslated region (3′UTR) microRNA (miRNA) binding sites of MRE11 gene are associated with decreased cancer risk but with shorter survival of CRC patients, which implies the role of miRNA regulation in CRC. The therapy of colorectal cancer utilizes oxaliplatin (oxalato(trans-l-1,2-diaminocyclohexane)platinum), which is often compromised by chemoresistance development. There is, therefore, a crucial clinical need to understand the cellular processes associated with drug resistance and improve treatment responses by applying efficient combination therapies. The main aim of this study was to investigate the effect of miRNAs on the oxaliplatin therapy response of CRC patients. By the in silico analysis, miR-140 was predicted to target MRE11 and modulate CRC prognosis. The lower expression of miR-140 was associated with the metastatic phenotype (p < 0.05) and poor progression-free survival (odds ratio (OR) = 0.4, p < 0.05). In the in vitro analysis, we used miRNA mimics to increase the level of miR-140 in the CRC cell line. This resulted in decreased proliferation of CRC cells (p < 0.05). Increased levels of miR-140 also led to increased sensitivity of cancer cells to oxaliplatin (p < 0.05) and to the accumulation of DNA damage. Our results, both in vitro and in vivo, suggest that miR-140 may act as a tumor suppressor and plays an important role in DSB DNA repair and, consequently, CRC therapy response.